IoT-Based Pill Monitor and Reminder for Medication Intake - G Jayandran, Shobanen; Mat Akir, Rohaida (Evolution in Electrical and Electronic Engineering, 2022)
Prescriptions can treat and prevent sickness. They needed to take their medication regularly to maintain proper levels. Taking drugs as recommended and following treatment programs are key to treating chronic diseases and preserving long-term health and well-being. Most people don’t take their prescriptions as prescribed because they’re too busy or forget. This project attempts to design an ESP32-based IoT pill monitor and reminder. It also creates a Blynk notification system. Most target Android users. This paper discusses a Blynk-based pill monitor and reminder box. The prototype includes an infrared sensor, ESP32, and a buzzer. Sensor sensitivity can be tested in multiple ways. Blynk’s input is infrared sensors. The sensitive infrared sensor can relay data to Blynk in 0.1 seconds. An infrared sensor recognizes a patient’s hand in 0.1s, silencing the alarm. Like Blynk’s time-based notifications, the buzzer will sound when coded. The findings of the tests indicate that the project can carry out its intended functions and provide the desired outcomes.